Performance and Applications of Graphene/Polymer Composites - Wang Qianyu (MATEC Web of Conferences)
Graphene/polymer composites possess high thermal conductivity, electrical conductivity, and mechanical properties, making them ideal structural materials. They have broad application prospects in the aerospace, electronic information, and communication fields. Traditional polymer materials tend to have low decomposition temperatures and poor thermal stability. The introduction of graphene can change this phenomenon to a certain extent, making the application of composites in high-temperature environments possible. This paper presents the preparation methods for graphene/polymer composites, including in-situ polymerization, solution blending, and melt blending, while examining how different fabrication processes affect the material characteristics during manufacturing. Additionally, it reviews these polymer composites’ thermal, mechanical, and electrical properties and demonstrates recent global applications of graphene-based composite materials across various fields. Graphene/polymer composites have broad application prospects in aerospace, medicine, and other fields. Optimizing the preparation process and properties can enhance the composites’ performance to meet the needs of industrial production. This is also the challenge facing the next step in the development of graphene/polymer composites. Composite materials possess excellent physical and chemical properties, such as thermal conductivity, toughness, and electrical conductivity, which endow them with great potential for applications and bring more economic and social value.